2010
DOI: 10.1094/pdis-94-3-0329
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Fungicide Resistance Frequency and Population Structure of Pyricularia oryzae after Discontinuance of MBI-D Fungicides

Abstract: The changes in fungicide resistance frequency and population structure of the rice blast fungus Pyricularia oryzae were monitored after the discontinuance of melanin biosynthesis inhibitor targeting scytalone dehydratase (MBI-D) fungicides use in Saga Prefecture, Japan. After discontinuance in 2003, the frequency of resistant isolates decreased from 71.8% in 2002 to 25% in 2003, and became undetectable in 2007. The initial marked decrease was due to a decline of isolates possessing the predominant haplotype, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
31
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 27 publications
1
31
0
Order By: Relevance
“…However, evolving resistance to some cMBIs that inhibit dehydration steps has become a problem in rice blast control as well as other plant diseases. 20) Tolprocarb, which is being developed by Mitsui Chemicals Agro, Inc., showed a high controlling effect on rice blast by both nursery box application and broadcasting on paddy rice (data not shown), and its practical value has been verified. Therefore, in considering the possibility of cross-resistance, clarifying tolprocarb's target site becomes of paramount importance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, evolving resistance to some cMBIs that inhibit dehydration steps has become a problem in rice blast control as well as other plant diseases. 20) Tolprocarb, which is being developed by Mitsui Chemicals Agro, Inc., showed a high controlling effect on rice blast by both nursery box application and broadcasting on paddy rice (data not shown), and its practical value has been verified. Therefore, in considering the possibility of cross-resistance, clarifying tolprocarb's target site becomes of paramount importance.…”
Section: Discussionmentioning
confidence: 99%
“…However, developing resistance to some cMBIs that inhibit dehydration steps has been a problem in controlling rice blast and other plant diseases. 20) For effective disease control, fungicides having different modes of action are required.…”
Section: Introductionmentioning
confidence: 99%
“…However, the evolution of resistance to conventional MBIs that inhibit dehydratase has become a problem for the control of rice blast. 16) Tolprocarb developed by Mitsui Chemicals Agro, Inc., showed a high controlling effect on rice blast by both nursery-box application and broadcasting on paddy rice. 19) In our previous paper, 20) we demonstrated that tolprocarb inhibited PKS activity with an IC 50 =0.03 µM.…”
Section: Discussionmentioning
confidence: 99%
“…[13][14][15] However, the development of resistance to conventional MBIs that inhibit dehydratase has posed a problem for controlling rice blast and other plant diseases. 16) Therefore, fungicides with different modes of action are required to combat the development of resistance to the currently used fungicides.…”
Section: Introductionmentioning
confidence: 99%
“…Suzuki et al monitored the emergence frequency of resistant isolates in fields in the Kyushu area after ceasing MBI-D applications and showed that the frequency had declined. 6) This indicates that after several years with no applications, the resistant populations decreased. Thus, MBI-Ds may again provide adequate disease control.…”
mentioning
confidence: 98%